2011
DOI: 10.1111/j.1440-1681.2011.05504.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the function of the serotonin transporter in the vasculature of male and female rats

Abstract: Summary The serotonin transporter (SERT) handles serotonin (5-hydroxytryptamine, 5-HT) and is blocked by the antidepressant SERT inhibitors fluoxetine and fluvoxamine. While the importance of SERT in the central nervous system is clear, SERT also functions in the peripheral vasculature. We tested the hypothesis that vasculature from female rats has increased SERT function compared to male rats because females are more responsive to SERT inhibitors.In addition to in vitro experiments, we imposed the challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Linder et al (2011) demonstrated a 50% decrease in the absolute magnitude of blood pressure fall to chronically infused 5-HT in both male and female SERT-knockout compared to wild type rats. While a serotonergic system, including SERT, exists in peripheral vasculature (Linder et al, 1008; Ni et al, 2006), it is difficult to imagine a mechanism whereby loss of SERT in the vasculature would reduce the ability of chronically infused 5-HT to decrease blood pressure.…”
Section: Discussionmentioning
confidence: 92%
“…Linder et al (2011) demonstrated a 50% decrease in the absolute magnitude of blood pressure fall to chronically infused 5-HT in both male and female SERT-knockout compared to wild type rats. While a serotonergic system, including SERT, exists in peripheral vasculature (Linder et al, 1008; Ni et al, 2006), it is difficult to imagine a mechanism whereby loss of SERT in the vasculature would reduce the ability of chronically infused 5-HT to decrease blood pressure.…”
Section: Discussionmentioning
confidence: 92%
“…Most studies on the evaluation of serotonin transport via SLC6A3, SLC6A4/5‐HTT/SERT, SLC18A2 and SLC22A3 by chromatographic techniques have used HPLC–EC, usually with an octadecylsilyl (C 18 ) column (Table ). Serotonin has been determined in brain dialysates, cochlear supernatants, plasma and various tissues by HPLC–EC (Armando et al, ; Callaghan et al, ; Cedeño et al, ; Choi et al, ; Fazzino et al, ; Feng et al, ; Huff et al, ; Kim et al, ; Kish et al, ; Kreiss et al, ; Linder et al, , , ; Nakatani et al, ; Ni et al, ; Ni et al, ; Pazzagli et al, ; Reader et al, ; Ren‐Patterson et al, ; Sánchez et al, ; Taylor et al, ; Tsuruoka et al, ; Vicente‐Torres et al, ; Vogel et al, ; Wei et al, ; Zhang et al, ; Zhou et al, ) and by HPLC–FL (Huang et al, ). Fanzzino et al demonstrated serotonin determination in human monocytes and lymphocytes (Fazzino et al, ).…”
Section: Transport Of Endogenous Compounds As Determined By Chromatogmentioning
confidence: 99%
“…Кроме того, есть сведения о существовании систем синтеза, захвата, выделения и расщепления 5-HT клетками эндотелия артерий и вен [24]. По мнению авторов, проводивших исследование на генетически нокаутированных по SERT-генам крысах, указанная транспортная система предупреждает десенситизацию 5-HT 2 -рецепторов, сохраняя тем самым способность сосуда к вазоконстрикции [21].…”
Section: синтез депонирование и высвобождение серотонина обеспечиваunclassified
“…Гладкие мышцы сосудистой стенки способны расслабляться вследствие активации 5-НТ 7 -рецепторов [8,30] -это результат прямого действия 5-HT. Вместе с тем 5-HT 1B/1D -, 5-HT 2A -рецепторы эндотелия и 5-HT 2B -рецепторы гладких мышц обеспечивают вазоконстрикцию [21,22].…”
Section: роль серотониновых рецепторов в регуляцииunclassified